2018
DOI: 10.31219/osf.io/tbq3n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disagreeing about development: An analysis of parent-teacher agreement in ADHD symptom trajectories across the elementary school years

Abstract: Objectives It is well‐known that in cross‐sectional analyses, agreement between informants is modest as best when rating attention‐deficit/hyperactivity disorder and other disruptive behaviour disorder symptoms. We here aimed to develop recommendations for the use of multi‐informant data in the context of longitudinal developmental analyses that examine symptom trajectories over time. Method Using parallel process modelling, we estimated parent–teacher agreement in inattention and hyperactivity/impulsivity sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Inattention and hyperactivity/impulsivity have shown differing patterns of results in terms of informant discrepancy. For example, Murray et al [ 5 ] found in a previous study in the current sample that while teachers tend to report higher levels of inattention on average, parents are more likely to report higher levels of hyperactivity/impulsivity. There is also evidence that inattention and hyperactivity/impulsivity differ in terms of their developmental trajectories.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Inattention and hyperactivity/impulsivity have shown differing patterns of results in terms of informant discrepancy. For example, Murray et al [ 5 ] found in a previous study in the current sample that while teachers tend to report higher levels of inattention on average, parents are more likely to report higher levels of hyperactivity/impulsivity. There is also evidence that inattention and hyperactivity/impulsivity differ in terms of their developmental trajectories.…”
Section: Discussionmentioning
confidence: 73%
“…The ‘cross-context’ requirement of DSM-5 creates a challenge, however, because parents and teachers frequently disagree on the severity of ADHD symptoms displayed by a child. In a meta-analysis of multi-informant studies, for example, the average correlation between parent and teacher- reported ADHD was only .43 for inattention and .42 for hyperactivity/impulsivity [ 4 ], with studies published since broadly replicating these figures [ 5 , 6 ]. The modest agreement between parents and teachers is not merely due to measurement error or informant biases (although both undoubtedly do contribute).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we used only teacher reports of symptoms to construct our mental health trajectories. This allowed us to avoid common rater bias [ 38 ] when assessing the relations between trajectories and covariates (which were based on parent reports and youth self-reports); however, previous evidence suggests young people show different symptoms in different contexts and/or in interaction with different informants [ 12 , 27 ]. This makes it important to assess the generalisability of conclusions across reports from different informants.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were from the Zurich Study on Social Development from Childhood to Adulthood (z-proso). z-proso is a normative, community-ascertained longitudinal study based in Zurich, Switzerland with a substantive focus on the development of core dimensions of psychosocial functioning, including ADHD symptoms (Murray, Booth, Eisner et al, 2019;Murray et al, 2017aMurray et al, , 2017bMurray et al, , 2018Murray et al, , 2020. It has collected, among other data, information on child mental health and behavior problems, substance use, socioemotional skills, peer problems, school issues, parenting, media use, leisure time activities, and life events.…”
Section: Participantsmentioning
confidence: 99%